The Yellowknife greenstone belt and underlying Central Slave Cover Group, Slave craton, Canada: constraints and questions arising from a U–Pb dating study - Ketchum, John W.F.; Bleeker, Wouter; Falck, Hendrik; Jackson, Valerie A. (Canadian Journal of Earth Sciences, 2025)
Legacy U–Pb isotopic data are reported for the Mesoarchean Central Slave Cover Group and Neoarchean Yellowknife greenstone belt, Slave craton, Northwest Territories, Canada. In two locations north of the City of Yellowknife, exposures of cover group rocks occur beneath mafic volcanic and subvolcanic units traditionally assigned to the basal Chan Formation of the Kam Group. Both cover group occurrences contain felsic volcanic tuff units that yield eruption ages of 2853 + 2/−1.5 Ma and 2826 ± 1.5 Ma. The younger tuff is underlain by felsic volcaniclastic schist with a dominant, basement-aged detrital zircon population that was deposited after 2840 ± 6 Ma. Near the south end of the exposed greenstone belt, a felsic tuff within the Octopus Formation provides an age of 2699 ± 3 Ma, confirming that this formation is not part of the Central Slave Cover Group. A pillowed basalt flow within the Chan Formation is cut by a composite gabbro dyke dated as 2738 +3.5/−3 Ma. However, a more general ca. 2730–2740 Ma age interpretation for this dyke may be appropriate due to the potential for complex lead loss behaviour in the dated baddeleyite fractions. Younger U–Pb zircon and monazite ages reported herein (2710–2706 Ma) contribute to our understanding of felsic magmatic and gold-mineralizing events that influenced later development of the Yellowknife greenstone belt. Although the depositional history of the autochthonous Central Slave Cover Group is becoming better known, questions remain regarding the age and tectonomagmatic affinity of adjacent mafic volcanic rocks traditionally assigned to the Kam Group and correlative assemblages. Are some of these rocks actually part of the Central Slave Cover Group?